Medial meniscus extrusion and varus tilt of joint line convergence angle increase stress in the medial compartment of the knee joint in the knee extension position ‐finite element analysis‐ - Takuhei Kozaki; Daisuke Fukui; Ei Yamamoto; Daisuke Nishiyama; Manabu Yamanaka; Akimasa Murata; Hiroshi Yamada (Journal of Experimental Orthopaedics)
Abstract Purpose Although it has been recognized that the medial meniscus extrusion (MME) leads to progressive cartilage loss and osteoarthritis (OA), about 20% of cases with MME had minor symptoms and poor progression of knee OA. However, it is still unclear which patients will have minimal symptoms or will not progress to degeneration. The purpose of this study is to compare the effect of the relationship between the MME and Joint line convergence angle (JLCA) on knee stress with the finite element (FE) analysis method. Methods The 65 year‐old female was taken computer tomography (CT) from thigh to ankle. A 3‐dimentional nonlinear FE model was constructed from the patient’s DICOM data. We made the six models, which was different from JLCA and MME. Contact stresses on the surfaces between femoral and tibial cartilages and both side of meniscus are analyzed. Results As the JLCA or MME increased, the stress load on the medial compartment increased. The effect of MME was stronger on the femoral side, while the effect of JLCA was stronger for the tibia and meniscus. If the JLCA was tilted valgus, the stress in the medial compartment did not increase even in the presence of MME. Conclusions This study revealed that the MME is associated with increased a stress loading on medial compartment structures. Furthermore, this change was enhanced by the varus tilt of the JLCA. In the case of valgus alignment, the contact pressure of the medial compartment did not increase so much even if with the MME. Level of evidence Level V